Cardiovascular Effects of Cocaine: Cellular, Ionic and Molecular Mechanisms - Turillazzi, E.; Bello, S.; Neri, M.; Pomara, C.; Riezzo, I.; Fineschi, V. (Current Medicinal Chemistry, 2012)
Cocaine is a widely abused drug responsible for the majority of deaths ascribed to drug overdose. Many mechanisms have been proposed in order to explain the various cocaine associated cardiovascular complications. Conventionally, cocaine cardiotoxicity has been thought to be mediated indirectly through its sympathomimetic effect, i.e., by inhibiting the reuptake and thus increasing the levels of neuronal catecholamines at work on adrenoceptors. Increased oxidative stress, reactive oxygen species, and cocaine-induced apoptosis in the heart muscle have suggested a new way to understand the cardiotoxic effects of cocaine. More recent studies have led the attention to the interaction of cocaine and some metabolites with cardiac sodium, calcium and potassium channels. The current paper is aimed to investigate the molecular mechanisms of cocaine cardiotoxicity which have a specific clinical and forensic interest. From a clinical point of view the full knowledge of the exact mechanisms by which cocaine exerts cardio – vascular damage is essential to identify potential therapeutic targets and improve novel strategies for cocaine related cardiovascular diseases. From a forensic point of view, it is to be underlined that cocaine use is often associated to sudden death in young, otherwise healthy individuals. While such events are widely reported, the relationship between cardiac morphological alterations and molecular/cellular mechanisms is still controversial. In conclusion, the study of cocaine cardiovascular toxicity needs a strict collaboration between clinicians and pathologists which may be very effective in further dissecting the mechanisms underlying cocaine cardiotoxicity and understanding the cardiac cocaine connection.
Keywords: drug overdose